1975
DOI: 10.1177/004051757504500211
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Lanthionine and Lysinoalanine as N-Trifluoroacetyl n-Butyl Esters by Gas-Liquid Chromatography

Abstract: A gas-liquid chromatographic method was explored for the analysis of lanthionine and lysinoalanine as well as lysine, cystine, and S -carboxyethylcysteine in chemically modified wool samples. The amino acids in the wool hydrolyzate were converted to n-butyl esters of N-trifluoroacetyl derivatives according to the method of Gehrke et al. The retention indices of the five amino acids mentioned above as well as other protein amino acids such as proline, phenytalanine, histidine (as mono and diacyl derivatives), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Gas-liquid chromatography has been also utilized (Sakamoto et al, 1975(Sakamoto et al, ,1977Hasegawa and Okamoto, 1980;Hasegawa and Iwate, 1982). All employ the use of trifluoroacetylbutyl esters and a means to volatilize the hydrolysate mixture before analysis.…”
mentioning
confidence: 99%
“…Gas-liquid chromatography has been also utilized (Sakamoto et al, 1975(Sakamoto et al, ,1977Hasegawa and Okamoto, 1980;Hasegawa and Iwate, 1982). All employ the use of trifluoroacetylbutyl esters and a means to volatilize the hydrolysate mixture before analysis.…”
mentioning
confidence: 99%
“…The higher the temperature, the longer the time, and the stronger the alkali, the more lysinoalanine formed (Nos. [8][9][10][11][12][13][14], and decreased in too severe conditions (Nos. 15,16).…”
Section: Lysinoalanine Formation By Alkali-treatment In Various Proteinsmentioning
confidence: 99%
“…1O , 11) On the EGA column (1.5 m X 3 mm I. D.), BTFA-Iysinoalanine was eluted midway in the cource of programed temperature, at about 178°C, and the separation from the other BTFA-amino acids were not good. On the other hand, on the OV-17/0V-210 mixed column, BTFA-Iysinoalanine was eluted at 14 min after the temperature reached to isothermal condition at 225°C, while most of the amino acid derivatives were eluted between 80 a C to 225°C (Fig.…”
mentioning
confidence: 99%
“…The determination of lysinoalanine has here tofore been made by ion exchange chromato graphy such as amino acid autoanalyzer.4,5) A related cross-linked amino acid, ornithino alanine, was also detected by this method, while the separation of both the compounds was not good.6) Thin layer chromatography of lysinoalanine was also reported.7) Gehrke et al 8,9) have studied in a series on gas-liquid chromatography (GLC) of amino acids, in which they analyzed gas chromatographically the N-trifluoroacetyl-O-butyl esters (BTFAamino acids) and trimethylsilyl (TMS) deriva tives of amino acids. Sakamoto et al 10,11) have reported on GLC and mass spectrometry of BTFA-derivatives of lanthionine, lysino alanine and S-carboxyethylcysteine in chemi cally modified wool fibers.…”
mentioning
confidence: 99%